2010
DOI: 10.1002/chem.200902817
|View full text |Cite
|
Sign up to set email alerts
|

A Rigid Dinuclear Ruthenium(II) Complex as an Efficient Photoactive Agent for Bridging Two Guanine Bases of a Duplex or Quadruplex Oligonucleotide

Abstract: The rigid dinuclear [(tap)(2)Ru(tpac)Ru(tap)(2)](4+) complex (1) (TAP=1,4,5,8-tetraazaphenanthrene, TPAC=tetrapyridoacridine) is shown to be much more efficient than the mononuclear bis-TAP complexes at photodamaging oligodeoxyribonucleotides (ODNs) containing guanine (G). This is particularly striking with the G-rich telomeric sequence d(T(2)AG(3))(4). Complex 1, which interacts strongly with the ODNs as determined by surface plasmon resonance (SPR) and emission anisotropy experiments, gives rise under illumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…As a function of increasing illumination times, the faster migrating adduct, giving the most intense spot after 3 min illumination, decreases in favour of the less migrating and finally non-migrating bands. The occurrence of covalent adducts with this telomeric sequence has been proven by nano-electrospray ionization analyses on the dialysed solution after illumination [46]. These analyses, complicated by the presence of a mixture of products, clearly showed the presence of photo-adducts corresponding to the addition of more than one complex on the telomeric sequence and indicated most probably the appearance of photo-cross-linked species inside the telomer.…”
Section: Applications For Bi-adduct Formation With Two Absorbed Photomentioning
confidence: 99%
“…As a function of increasing illumination times, the faster migrating adduct, giving the most intense spot after 3 min illumination, decreases in favour of the less migrating and finally non-migrating bands. The occurrence of covalent adducts with this telomeric sequence has been proven by nano-electrospray ionization analyses on the dialysed solution after illumination [46]. These analyses, complicated by the presence of a mixture of products, clearly showed the presence of photo-adducts corresponding to the addition of more than one complex on the telomeric sequence and indicated most probably the appearance of photo-cross-linked species inside the telomer.…”
Section: Applications For Bi-adduct Formation With Two Absorbed Photomentioning
confidence: 99%
“…From selected structures from the preliminary MD simulations for noncovalent Ru-TAT/ODN complexes, the structures of the Ru-TAT-ODN covalent adducts were obtained as described previously. [46] The MD simulations of Ru-TAT and Ru-TAT-ODN were performed with the CHARMM force-field, [47] and water was considered explicitly through the use of the water box model. The MD simulations were performed in (N,V,T) at 300 K with a time step of 1 fs from 1 ns to 10 ns.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…Ruthenium(II) complexes have prominent DNA binding properties. 22 Thomas et al reported that the dinuclear tppz-based systems could bind with high affinity to quadruplex DNA at high ionic strengths through the 22-mer d(AG 3 3 ] human telomeric sequence. 16,17 Such complexes can tightly intercalate between the duplex DNA base pairs and stabilize the DNA.…”
Section: Introductionmentioning
confidence: 99%